2006
DOI: 10.1007/s10750-005-1168-3
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Nutrient Competition and Allelopathic Effects in Suppression of the Green Alga Scenedesmus obliquus by the Macrophytes Chara, Elodea and Myriophyllum

Abstract: Possible allelopathic effects of substances released from the macrophytes Chara globularis, Elodea canadensis, Myriophyllum spicatum on the common green alga Scenedesmus obliquus were tested in the laboratory with plastic plants and untreated medium as controls. A two-phase approach was used in which first the effects of physical presence of plants was studied (phase I) followed by the effects of plant culture filtrates (phase II). In the presence of plastic plants growth was reduced only marginally, but stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Several authors wondered whether separating resource competition from allelopathy is at all realistic (Inderjit & del Moral, 1997;Lü rling et al, 2006;Lombardo et al, unpublished). Phosphorus and nitrogen limitation may affect the production and release of allelopathic compounds by submerged macrophytes (Gross, 2003b), as well as the response of the target organism (Reigosa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors wondered whether separating resource competition from allelopathy is at all realistic (Inderjit & del Moral, 1997;Lü rling et al, 2006;Lombardo et al, unpublished). Phosphorus and nitrogen limitation may affect the production and release of allelopathic compounds by submerged macrophytes (Gross, 2003b), as well as the response of the target organism (Reigosa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In shallow waterbodies there exists an antagonistic relationship between phytoplankton and macrophytes. In macrophytic zones, low water turbulence, reduced light intensity and low nutrient concentrations in water limit phytoplankton growth (Lürling et al, 2006;Muylaert et al, 2010). However, macrophytes also affect plankton through the release of allelochemicals into the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies also suggested that low molecular weight substances could be allelopathically active (anthoni et al 1980;BanKova et al 2001;van donK & van de Bund 2002;lürling et al 2006;KuraShov et al 2014). BanKova et al (2001) identified some volatile compounds but did not test them separately for possible inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%